National Identity in War-Torn Community - Ajduković, Dean (Array, 2002)
This paper studies the salience of national identity in a community profoundly divided along ethnic lines as a consequence of war. Members of two ethnic groups rarely communicate with each other, listen to different radio stations, read different newspapers, shop in different stores. The children, who do not have any personal memories of the war, go to separate schools and have almost no contact with the other ethnic group. In a divided community such as this one, the salience of national identity is a fact of everyday life. We hypothesised that members of both groups would score high on national identity measure due to the salience of national identity in such a divided community. According to the Social Identity Theory, we would expect members of the minority group to score higher on national identity than members of the majority group. However, the ongoing process of resettlement to Vukovar makes it difficult to determine which group is minority and which is majority in terms of the number of people currently living in Vukovar. Therefore we expected that members of both ethnic groups would score high on national identity. The NAIT (National Identity Scale) was administered to 456 children of Vukovar. The scale measures national identity defined as an attachment to one's nation and the sense of belonging to it. The national identity was analysed with regards to ethnic background, age and gender of participants. The analyses indicated that all children scored high on the national identity scale. There were no differences in national identity between members of the minority and the majority ethnic groups, nor with regards to the age. Boys, however, scored higher on national identity scale.